Incidence, outcome, and prognostic factors of prolonged mechanical ventilation among children in Chinese mainland: a multi-center survey - Zhang, Zhengzheng; Cai, Xiaodi; Ming, Meixiu; Huang, Li; Liu, Chengjun; Ren, Hong; Qu, Dong; Gao, Hengmiao; Cheng, Yibing; Zhang, Furong; Yang, Zihao; Xu, Wei; et al. (Frontiers in Pediatrics, 2024)
care unit，chronic respiratory failure Abstr act Objective To evaluate the incidence, outcome, and prognostic factors of prolonged mechanical ventilation (PMV) in children in Mainland China. Methods A prospective study was conducted in 11 pediatric intensive care units (PICUs) from May 1, 2021, to April 30, 2022. All pediatric patients on mechanical ventilation meeting the criteria for PMV were included in the study. Results Out of 5292 patients receiving mechanical ventilation, 278 children met the criteria for PMV (5.3%). After excluding case with incomplete data or lost to follow-up, the study included 250 patients.Among them, 115 were successfully weaned from mechanical ventilation, 90 died, and 45 were still on mechanical ventilation. The six-month survival rate was 64%. tracheotomy timing emerged as an independent predictor of failure to wean from PMV, with an OR of 1.08, (95% CI: 1.01-1.16; P=.030) Conclusions The study revealed a 5.3% incidence of PMV in children requiring mechanical ventilation in China. The use of vasoactive agents and a higher PELOD-2 score at PMV diagnosis were significantly associated with an increased risk of PMV death, whereas early rehabilitation intervention was identified as crucial for improving patient outcomes. The timing of tracheostomy was identified as a high-risk factor for failure to wean from mechanical ventilation.